8x + 5z - 4x + 3z + 6 = 8x - 4x + 5z + 3z - 6 = 4x + 8z - 6
-4x + 5 + 3x + 6 = -x + 11
2x + 3 = -92x = -12x = -6
4x + 2 + 6 = 2 4x + 8 = 2 4x = -6 x = -6/4 = -3/2
-6x-6 -or- -6(x+1)
It is -4x - 4
The answer to the math problem of 5x plus 7x-4x 6 is -12.
8x - 7y + 6
6x+4 = x+12+4x-6 6x-x-4x = 12-6-4 x = 2
Because (x plus 3x) is 4x, and (-5 + 11) is 6.
5x + 6 = 1 / 4(13x-11)(5x+6)(4)(13x-11)= 14(65x2-55x+78x-66)=1260x2 +92x-264-1=0260x2+92x-263=0Graph y = 260x2 +92x -263 and find its zero or use the quadratic formula
-4x + 2 = 6 -4x = 6 - 2 -4x = 4 x = 4 / -4 x = -1